SKEPTIS AKADEMIS SULAIMAN AS TERHADAP ARGUMENTASI POLITIS DAN TEOLOGIS HUD HUD DALAM WAHANA SEMIOTIKA ALGIRDAS GREIMAS - Asep Muharam (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This study aims to discuss the academic scepticism of Prophet Solomon as to Hud hud's political and theological argumentation in the semiotic analysis of Algirdas Julien Greimas ' narratology. This study is a qualitative type of research with an analytical approach semiotics narratology Algirdas Julien Greimas and literature study methods with primary sources is the Qur'an and its interpretation and books relevant to the focus of research. The formal object is the semiotic analysis of narratology A.J Greimas and his material object were the academic sceptics of Solomon as to Hud hud's political and theologist argumentation. The results and discussion of the study showed that the story of Prophet Sulaiman as with Hud hud in semiotic analysis of narratology A.J Greimas shows the structure of birth that the Prophet Solomon as character-wise and peace-loving, caring and responsibility. Meanwhile, the inner structure is academic scepticism towards Hud's political and theological arguments.